THE INFLUENCE OF CHATGPT USAGE ON STUDENT LEARNING OUTCOMES IN THE ALGORITHM AND PROGRAMMING COURSE AT UNIVERSITAS AL-KHAIRIYAH - Swastika, Rulin; Rahayu, Didda Yuliana (Institut Bakti Nusantara, 2025)
This study aims to analyze the influence of ChatGPT usage on student learning outcomes in the Algorithms and Programming course at Universitas Al-Khairiyah. The background of this research is rooted in the growing adoption of artificial intelligence (AI) technologies in education, particularly in supporting the understanding of complex concepts. A quantitative approach was used, with data collected through a linear scale (1–4) questionnaire distributed to students. The analysis results show a strong and significant relationship between the use of ChatGPT and student learning outcomes, with a correlation value of 0.672. Furthermore, the coefficient of determination (R²) of 0.452 indicates that ChatGPT usage contributes 45.2% to the variation in student achievement. These findings demonstrate that effective use of ChatGPT can enhance students' conceptual understanding, task completion efficiency, and overall academic performance. Therefore, ChatGPT can be considered a promising learning tool to improve the quality of education in the field of technology and informatics.